THE ENFORCEMENT OF CRIMINAL LAW AGAINST ACTORS INVOLVED IN THE SELLING OF IMPORTED SECONDHAND CLOTHING (THRIFTING) IN SAMARINDA CITY - Rozy, Fahrul; Syarifuddin, La; Damanik, Amsari (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2026)
The phenomenon of importing used clothes or thrifting has grown rapidly in Samarinda City, in accordance with Law Number 7 of 2014 concerning Trade and Regulation of the Minister of Trade Number 40 of 2022 which prohibits the import of used clothes. This study aims to analyze effective criminal law enforcement strategies for sellers of imported used clothes who have transformed into digital entrepreneurs with increasingly sophisticated modus operandi. The results of the study show that the majority of business actors operate without adequate permits, creating an economic paradox in which these activities contribute positively to the community's economy but are detrimental to the rule of law and economic justice. Law enforcement faces obstacles in coordination between agencies. This study recommends a holistic and progressive law enforcement strategy through tripartite coordination between the Police, Customs and Excise, and the Trade Office that not only focuses on repressive law enforcement but also education, coaching, and developing a digital surveillance system to anticipate the innovation of the modus operandi of thrifting business actors in the future.